STRATEGI PENINGKATAN PENDAPATAN USAHATANI PADI SAWAH DI DESA BUKIT PARIAMAN DAN BUANA JAYA KECAMATAN TENGGARONG SEBERANG (Strategy Increasing Income of Lowland Paddy Farming (Oryza sativa L.) in Bukit Pariaman and Buana Jaya Villages Tenggarong Seberang Subregency) - HANIF SOFYAN; MARIYAH MARIYAH; NDAN IMANG (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2021)
Lowland paddy farming is one of income source of farmer besides others business. Income of lowland paddy farming is still low  therefore it is needed a strategy to increase income in order to increase farmer welfare. The purpose of this study was to determine strategy to increaseincome of lowland paddy farming. This research was conducted from February to April 2020 in Bukit Pariaman and Buana Jaya Villages, Tenggarong Seberang Subregency. Thedata were collected  primary and secondary data. The sampling method used purposive sampling method. Method of data analysis used the SWOT method. The result of this study indicates that aggressive strategy is needed toincrease income of lowland paddy farming in the research locations.